Biochemical characteristics of soft wheat grain associated with endosperm separation from bran and flour yield. Issue 3 (26th February 2020) - Ji, Taehyun; Ma, Fengyun; Baik, Byung‐Kee
Abstract: Background and objectives: Endosperm separation from bran during wheat grain milling has a substantial influence on flour yield, whereas little is known about the endosperm characteristics affecting its detachment from bran. The associations of the outer endosperm characteristics with its separation from bran during milling, and subsequently with flour yield, were determined. Findings: The yields of flour and remnant endosperm of bran (REB) for ten soft red winter wheat varieties ranged from 66.7% to 75.9% and 1.7% to 3.7%, respectively. The ash, water‐soluble AX, and β‐glucan contents of the REB exhibited significant relationships with flour yield at p  < .05. Wheat varieties of >75% flour yield exhibited higher ash and lower water‐soluble AX contents of the REB than the varieties of <68% flour yield. The ash and water‐soluble AX contents of flour also exhibited significant relationships with flour yield at p  < .01. Conclusions: The water‐soluble AX content of endosperm is implicated in the separation of endosperm from bran during milling of wheat grain. Significance and novelty: Wheat grain outer endosperm that is low in water‐soluble AX could positively contribute to flour yield because of its role in the efficient detachment of endosperm from bran during milling.